The PERCEPTION OF PAI STUDENTS ON THE IMPLEMENTATION OF KKNI CURRICULUM AT STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA: PERCEPTION OF PAI STUDENTS ON THE IMPLEMENTATION OF KKNI CURRICULUM AT STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Rabiatul Adawiyah (Cendekia Madani Nusantara, 2023)
This study aims to see and find out how students' perceptions or views of the implementation of the KKNI at the State Islamic University of North Sumatra, especially students of the Islamic Religious Education study program. The focus of this research is to see the views of PAI students on the tasks contained in the application of the KKNI. These tasks are: Routine Assignments, Critical Book Review (CBR), Critical Journal Review (CJR), Mini Research, Engineering Ideas and Projects. The method used by researchers in this study is a qualitative method with a descriptive narrative study research approach. The research used data collection techniques by means of observation and interviews. The informants in this study were students of the Stambuk 2020 PAI study program who are currently in semester VI (six). And from the research process, the results were obtained that PAI students had a good perception of the implementation of the KKNI at the State Islamic University of North Sumatra.